Analisis Kapasitas SMP Muhammadiyah 6 Jenawi Dalam Menghadapi Ancaman Bencana Tanah Longsor - Arif Nur Fajriyanto; Eka Septiyaningsih; Nida Hanifah; Bagas Anindra Murdiansyah; Ramadhini Rudi Santoso; Fitri Nur Aini (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
Disaster capacity needs to be increased to reduce disaster risk. The purpose of this study was to determine the level of knowledge of the Muhammadiyah 6 Jenawi Middle School students in facing the threat of landslides and to know the physical capacity of the 6-Gen. Muhammadiyah Middle School building. This type of research is quantitative descriptive. The study population was residents of the 6 Jenawi Muhammadiyah Middle School. The study sample consisted of 30 student respondents, 12 teacher respondents, and a school principal. The results showed that students' knowledge was 76.3%, teachers were 83.9% and the principal's policy was 76.2%. Where the majority of teacher knowledge is at a fairly high level and is followed by students who are also quite good, it depends on the policies applied by the principal. The physical condition of school buildings is at the level of 53.3% in accordance with safe buildings in landslide preparedness that can be considered sufficient in preparedness to face the threat of landslides.